Controversies in the Management of Central Cord Syndrome: The State of the Art. (4th April 2018) - Wagner, Peter J.; DiPaola, Christian P.; Connolly, Patrick J.; Stauff, Michael P.
Abstract : Traumatic central cord syndrome is an incomplete spinal cord injury characterized primarily by disproportionate motor and sensory loss in the upper extremities compared with the lower extremities. Initial management of central cord syndrome includes immobilization in a rigid cervical orthosis, maintaining mean arterial pressure, and performing serial neurologic examinations. Treatment with high-dose methylprednisolone is no longer recommended for the treatment of central cord syndrome. Central cord syndrome is generally treated surgically, but the timing and surgical approach depend on injury characteristics, including the injury pattern, neurologic examination and its evolution, and patient comorbidities. Early surgery may be performed safely in the appropriate patient, but there is little evidence to support the notion that earlier surgery affects neurologic outcomes.